Tadris al Ta’biir al Syafahii bi al Thoriqoh al Ittishooliyah li Thulaab Qism Ta’lim al Lughoh al ‘Arabiyyah bi Jaami’ati Muhammadiyah Tangerang - Faedurrohman, Faedurrohman (Universitas Islam Negeri Raden Intan Lampung, 2018)
مستخلص البحث:ينطلق هذا البحث من مشكلة التي يواجهها طلاب قسم تعليم اللغة العربية بجامعة محمدية تانجرانج، حيث صعوبتهم على ممارسة التعبير الشفهي. ويهدف هذا البحث لكشفها، ولوصف الخطة الاجرائية عما يتعلق بتدريس التعبير الشفهي بالطريقة الاتصالية وأثرها في ترقية كفاءة التعبير الشفهي لطلاب قسم تعليم اللغة العربية في جامعة محمدية تانجرانج. هذا البحث بحث نوعي، ويُخْتَصّ هذا البحث في دراسة حالة لأنها يُقَصّده الباحث لمعرفة المشكلة التي يواجهها الطلاب في التعبير الشفهي ومراحل تدريسه بالطريقة الاتصالية التي تجري في الفصل وأثرها شاملا وعامقا. وتشير نتيجة هذا البحث: الأول، أن المشكلة التي يواجهها الطلاب في تدريس التعبير الشفهي هي: أ). قلة التدريبات اللغوية الشفوهية، ب). قلة حفظ المفردات الموضوعية، ج). قلة التواصل بين الطلاب باللغة العربية، د). قلة اهتمام بالمواد المدروس، هـ) أن التعبير الشفهي الذي يمارسه الطلاب غير منتَظِم. الثاني، أن تدريس التعبير الشفهي بالطريقة الاتصالية على ثلاث مراحل إجرائية، وهي الخطة، والتنفيذ، والتقويم. والثالث، إن استخدام الطريقة الاتصالية فعال في ترقية كفاءة التعبير الشفهي.الكلمات المفتاحية: تدريس، التعبير الشفهي، الطريقة الإتصالية AbstrackThis research departs from the problems faced by the students of the Arabic Language Education Department of Muhammadiyah University in Tangerang in the ta'bir syafahi (verbal expression) practice. The purpose of this study was to reveal the problems faced by students in teaching ta'bir syafahi and also the procedures for using communicative methods in teaching ta'bir syafahi and their effectiveness in improving ta'bir syafahi competencies in Arabic Language Education students at Muhammadiyah University in Tangerang. This study uses a qualitative approach; and including the type of case study because researchers want to know deeply and comprehensively about the problem ta'bir syafahi experienced by students, the stages of teaching, and the impact of the application of communicative methods in ta'bir syafahi learning. The results of this study indicate that: First, the problems faced by students of the University of Muhammadiyah Tangerang in teaching ta'bir syafahi include: a). lack of oral language training, b). treasury of thematic mufradat is still minimal, c). the intensity of Arabic communication is still lacking, d). lack of attention to the material being taught, e). less systematic in conveying ideas. Second, the procedure for applying communicative methods in ta'bir syafahi includes three things, namely: a). Planning, b). Implementation, c). Evaluation. Third, the use of communicative methods is effective in improving the competency of ta'bir syafahi.Keywords: Communicative Method, Teaching, Ta'bir Syafahi